Seir epidemic model with two time delays. Issue 2 (2nd July 2016) - Waezizadeh, Tayebeh
Abstract: In this paper we introduce the SEIR epidemic model with latent and infectious time delays, which are denoted by ω and τ respectively. As follows we consider two different cases, ω = 0 and ω ≠ 0 ≠ τ . Stability near disease-free and endemic equilibrium points in different cases are investigated.